Một số nét về các phòng thí nghiệm tự động hóa hiện nay ở nước ta - Cát, Phạm Thượng; Lân, Vũ Như; Thắng, Nguyễn Thế (Journal of Computer Science and Cybernetics, 2016)
The workplan of the project VIE/89/002 “Data Processing Review” and the project KC-02-01 of National Science & Technology Program for Automation organized the study tours for data collections and analysis of the industrial automation in Vietnam. The data collection is based on brain storming sessions and interviews on site with selected sample firms/organizations. The analysis is based on methods to achieve the following objectives: 1) To determine the SWOT (Strength, Weaknesses, Opportunities and Threats). 2) To make the industry analysis for determining the level of five forces on industry attractiveness. 3) To determine the stage and level if IT usage in the selected sample firms/organizations.